Sukuk issuance in China: trends and positive expectations - Bo, Ding; Engku Ali, Engku Rabiah Adawiah; Saiti, Buerhan (EconJournals, 2016)
The paper assesses the potential and importance of Sukuk issuance in China. The research proposes that Sukuk can be used as an alternative financing instrument to materialize the “One Belt One road (OBOR)” strategy. Hong Kong as a gateway of China had launched two Sukuks in 2014 and 2015 respectively. This paper analyzes the two sovereign Sukuk issuances out of Hong Kong in the last 3 years. Meanwhile, by conducting un-structured interviews of the potential issuers and related scholars, it is found that Sukuk issuance in China will face some challenges such as policies and regulations of Sukuk, tax and stamp duty issues, investors’ protection, establishing of Shariah Supervisory Committee, etc. However “OBOR” initiative provides the best opportunity for Sukuk to move forward in China.